Special articleMagnetocardiography in clinical cardiology. Status quo and future applications - Leithäuser, Boris; Jung, Friedrich; Park, Jai-Wun (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2011)
Magnetocardiography (MCG) is a non-contact, non-invasive technique for the assessment of electromagnetic activity of the human heart. Theoretical considerations and comparative studies indicate different information content between MCG and electrocardiography (ECG). Although many questions about cardiac pathophysiology and electrophysiology can be answered by MCG studies, measurement of biomagnetism is still only marginally recognized as a valuable tool. Although MCG instrumentation (SQUIDs, MSR) and operation (liquid helium) are expensive and not available at the bedside, the gain of information drawn from the cardiac magnetic field is worth the effort. The MCG has superior sensitivity for ischaemic myocardium both at rest and under stress. Therefore, it may change one’s ideas of decision making about invasive procedures. Compared to scintigraphy, which is a cumbersome method with the need of radioactivity exposure to the patient, MCG is as easy as bicycle ergometry but with higher sensitivity. In terms of risk stratification for sudden cardiac death, it seems to be possible that MCG in the future will provide additional information as to which patient will not benefit from prophylactic defibrillator implantation. However, appropriate clinical studies are lacking. Most interestingly, MCG appears to be practical and informative in the diagnosis of cardiac arrhythmias, and has sufficient spatial accuracy necessary for clinical purposes. It seems realistic that MCG-based localization of arrhythmogenic spots may guide the operator’s ablation catheter, e.g. in patients with relapsing AF after a first successful ablation procedure. There is enough room for fantasy which question in clinical cardiology remains to be answered by MCG.